A Phenomenological Analysis of the Self-Regulatory Behaviours of a Group of Young Adults in a Vocational Education and Training Business Program - Liveris, Christine; Cavanagh, Robert (Australian Association for Research in Education (AARE), 2012)
National Vocational Education and Training (VET) reforms have resulted in an increasing proportion of young adults in VET programs in Western Australia. A challenge for practitioners is to help them develop skills and attributes to facilitate lifelong learning. A need for further research into the self-regulation behaviour of this cohort has been identified. The primary research question was: What are the self-regulation behaviours of a group of 18-24 year olds while preparing a business assessment? Specifically: What were their help-seeking behaviours? How did they manage their time and study environment? This phenomenological study was concerned with understanding self-regulation behaviour as it was perceived by eight VET business students and their teachers. Semi-structured interviews were undertaken after submission of a written task. Quality control was achieved through a combination of data from participant and teacher interviews, and the researcher's interpretations. The self-regulatory behaviours of these learners were dependent on a range of factors. Findings provide the basis for further research into personality and self-regulation behaviour; learning difficulties and self-regulation behaviour; and the impact of technology distractions on time and effort. This paper outlines the background, methodology, results and conclusions of this investigation.